2017
DOI: 10.21873/anticanres.11438
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerance of D,L-Methadone in Combination with Chemotherapy in Patients with Glioma

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Therefore, a first trial was conducted with glioma patients (grade II-IV) that received standard therapy, including TMZ, together with MTD. Although no final conclusions can be drawn from this retrospective study of small group size [ 6 ], the regime based on MTD as therapeutic has been widely discussed and propagated in social media. It, thus, became obvious that there is a strong need for more background data on MTD and its impact on TMZ-induced responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a first trial was conducted with glioma patients (grade II-IV) that received standard therapy, including TMZ, together with MTD. Although no final conclusions can be drawn from this retrospective study of small group size [ 6 ], the regime based on MTD as therapeutic has been widely discussed and propagated in social media. It, thus, became obvious that there is a strong need for more background data on MTD and its impact on TMZ-induced responses.…”
Section: Discussionmentioning
confidence: 99%
“…This was explained by assuming that MTD impacts doxorubicin uptake and attenuates its efflux, which would enhance the intracellular level of doxorubicin and, consequently, its cytotoxic activity [ 5 ]. Based on this work, a trial has been initiated treating glioma patients (grade II–IV) with MTD, which occurred independent of their neuro-oncological treatment [ 6 ]. In view of the patient heterogeneity, small group size and lacking stratification of the control group, a conclusion as to the therapeutic benefit of MTD in mono- or combined therapy could not be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore conceivable that the in vivo concentrations of methadone are even lower in GBM patients compared with nontumorous brain tissue, which was the subject of recent forensic studies investigating tissue concentrations of D and L methadone in the human brain [ 44 ]. A first study on the clinical feasibility of D,L-methadone in patients with recurrent GBM has used an ascending dosing protocol of D,L-methadone up to a maximum of 20–35 mg/day [ 10 ], which is about half of the dosage used in opioid addicts. Although in this study, the observed D,L-methadone-related toxicity was rather moderate and the 6-month progression free survival was found comparable to historic controls, the putative concentrations of D,L-methadone in the brain with this dose regimen are presumably significantly lower compared with the concentrations found effective in the in vitro study on GBM cells by Friesen and co-workers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] showed that D,L-methadone mediates enhanced apoptosis and increased sensitivity toward doxorubicin in established GBM cell lines by reversing deficient caspase activation and reducing intracellular cAMP levels. Furthermore, a recent retrospective report from 27 recurrent GBM patients treated with increasing D,L-methadone concentrations implies a moderate toxicity, while no efficacy data were reported due to the absence of a control arm in this study [ 10 ]. D,L-methadone is a μ-opioid receptor agonist, stimulating inhibitory G i -proteins, which in turn block adenylyl cyclase activity, followed by an decrease of cAMP levels [ 11 ].…”
mentioning
confidence: 95%
“…After reaching the maximal methadone dosage, the adverse side effects remained in four patients with mild to moderate obstipation (CTC grade 2–3; n = 3) and nausea (CTC grade 2; n = 1). The comparison of the progression free survival at 6 months (PFS-6) between the intervention group and a historic control group was not significant; however, mean overall survival was not reached ( Onken et al, 2017 ). This study gives a hint that methadone can be safely combined with standard tumor treatment.…”
Section: Antitumor Activities Of Methadonementioning
confidence: 86%